El dibujo infantil y su incidencia en el desarrollo de la creatividad en los niños y niñas del primer año de educación básica del Centro Educativo Particular Bilingüe María del Carmen, Escuela República de Francia y la Escuela Zoila Ugarte de Landivar de la ciudad de el Guabo, en el periodo 2012-2013. - Moralez Moralez, Grace Anabel (2013)
Child drawing in children is very important and indispensable, is a symptom of creativity, ability and observation of the environment through which allows the child to be incorporated into the medium and can have a clear intention to communicate situations, characters, emotions.